STRATEGI IDEAL PEMBERANTASAN KORUPSI DI INDONESIA - Farida Sekti Pahlevi (Al-Syakhsiyyah: Journal of Law & Family Studies, 2022)
Eradication of corruption must be carried out in a real and comprehensive manner in all areas of social, national and state life. The commitment of all parties in eradicating corruption must be strengthened by a firm, consistent, responsible and totality attitude. Important steps to enforce a just law, provide legal certainty, and benefit the community can be realized properly if they have strong beliefs from within all parties. Optimism in eradicating corruption must always exist within the parties involved. Steps starting from steps to improve the system, educational and campaign steps as well as repressive steps must be taken so that efforts to eradicate corruption in Indonesia can run and can face every obstacle that exists. This is expected to increase public confidence, investors, national pride, as well as create a deterrent effect, prevent potential corruptors, optimize the return of state or people's money and provide other positive impacts.